Effects of feeding diets containing heated hemp seed cake and phytase enzyme on the bone mineral of broiler chickens - Darmawan Arif; Ozturk Ergin (BIO Web of Conferences)
The purpose of the study was to investigate the impact of heated hemp seed cake and phytase enzyme inclusion into the diet on the mineral content of the tibia and femur in broiler chickens. Unsexed Ross broiler chicks (210 birds) were randomly allocated into 7 treatments and 6 replicates and reared for 42 days. The treatments were P1= diet based on corn-soybean base; P2= diet containing 15% of HSC; P3= P2 with 1000 FTU/kg phytase enzyme; P4: diet containing 15% of autoclaved HSC; P5= P4 with 1000 FTU/kg phytase enzyme; P6= diet containing 15% of oven-heated HSC; P7= P6 with 1000 FTU/kg phytase enzyme. The findings indicated that the inclusion of HCS in the diet resulted in enhancement (P<0.05) in the calcium content of the tibia. Dietary autoclaved HSC with phytase enzyme significantly increased (P<0.05) phosphorus and potassium of the tibia compared to soybean and raw HSC-based diet. However, the treatments had no impact (P>0.05) on the magnesium, and calcium to phosphorus ratio (Ca:P) of tibia. In the femur bone, dietary autoclaved HSC with phytase enzyme significantly improved (P<0.05) calcium compared to a diet based on soybean meal, raw HSC, and oven-heated HSC without phytase enzyme. Dietary autoclaved HSC with phytase enzyme significantly improved (P<0.05) phosphorus of the femur compared to soybean meal and autoclaved HSC-based diet and increased (P<0.05) potassium compared to soybean meal, raw HSC-based diet. The treatments did not significantly affect (P>0.05) the magnesium levels in the femur. It is concluded the dietary autoclaved HSC with phytase enzyme is effective in improving the calcium, phosphorus, and potassium of the tibia and femur bone of the broiler.